Avaliação da atenção básica em saúde no estado do Ceará :explorando concepções no nível central - Vasconcelos, Suziana Martins de (2006)
It is recognized, by means of the empirical comment, that the Model of Basic Attention, operacionalizado for the Strategy Health of the Family, still does not function in its fullness, a time that is not made use of systemize and validated mechanisms, for its monitoring and evaluation. Thus, structuralized in three components: the Project of Expansion of the Health of Família (PROESF), of the Health Department, which appeared with the objective to extend the attendance covering, objectifying in its third component: "Monitoring and Evaluation" the institutionalization of the evaluation in the basic attention, by means of the fortifying of the actions of monitoring and evaluation of the state secretariats of health. This study drift of a concrete experience in the operacionalization of the objective, having as objective to understand the experiences and perceptions of technician and managers of the Secretariat of the Health of the State of Ceará (SESA-CE) in relation to practical of developed evaluation and the monitoring in the local level. The methodology is enrolled in the qualitative boarding and the studied population encloses the responsible group for the basic attention (NUORG), key-informers for the understanding of the conceptions about the evaluation of the basic attention in health. We use the technique of focal group for the apprehension of the empirical data. From the reading and rereading of the narratives, three subjects had emerged central offices: nature and purposes of the evaluation; the experience with evaluation; and the space of the quality in the evaluation, that constitutes the central axle of our analysis. These subjects, in turn, are unfolded in dimensions, that clarify the narrow interface of the empirical categories in the narratives of the informers. Amongst the main findings it is proven that the conception of evaluation formulated for the informers not they are in agreement with the practical one of service of the group, the evaluation process is not taken the handle and the experiences and evaluation practice of health if they always give in reply to a verticalized demand. In addition, the gotten results do not contribute for a reformularization accomplish of proposals and concrete interventions in the service. Also the involved ones in the service do not participate of the process of quarrel of the evaluations of programs and services of health, what it makes with that the evaluation concept little is understood by the informers, becoming consumed it in the process of operacionalization of the activities in the services. Moreover, the consuming also happens due the interruptions in the avaliative process and weak envolvement of the actors of the health service. The term quality is used, simply, in the objective dimension, consonant the traditional avaliative model. In the avaliative experiences, the normative approach prevails, with quantitativist boarding, showing a distance in relation to the qualitative-participative approach.